Management of Kaphaja Yoni Vyapat by Panchavalkala Arka w.s.r to Vuvlovaginal Candidiasis- A Case Report (AYUSHDHARA, 2021)
Vulvovaginal candidiasis is caused due to different candida species, most commonly C.albicans. It occurs in 1-14% of all women of reproductive age throughout the world and its prevalence in India is estimated to be 30% It may be physiological condition but when turns into pathological, produces associated symptoms such as pruritus, backache, white discharge with foul smell and alters the PH of the vaginal flora. This can be correlated to the Lakshanas of Kaphaja yoni vyapat, where there will be Kaphavrudhi all over the body. Management of this condition is by using Ruksha, Katu, Ushna dravyas. Sthanika Chikitsa such as Yoni Prakshalana (douching), Yoni Pichu (tamponing per vagina), Yoni Varti (local use of pessaries) and Yoni Dhoopana (fumigation) have been mentioned and these modalities are found effective in treating Kaphaja Yoni Vyapat. During the current era, many vaginal washes is available easily over the counter and women prefers using such preparation, when they come across vaginal itching and discomfort and abnormal vaginal discharge. Here is an effort to prepare a colorless, odorless solution, adopting the principals of Ayurveda which can be convenient for washing easily at home for women. Methodology: Here is a case report of a patient with complaints of Kaphaja Yoni Vyapat diagnosed vaginal candidiasis by swab smear test selected from outpatient department of SDM Ayurveda hospital Hassan. Panchavalkala Arka will be given to the pts and advised to wash it twice a day for 7 days. Results: Local therapies such as Sthanika Chikitsa have lot of potential in treating Yoni Vyapad and in Panchavalkala Arka the drugs with its Guna Karma helps in breaking the Samprapti of Kaphaja Yoni Vyapat. Discussion: PVQ Arka is a liquid preparation obtained using Arkayantra which contains the 5 Ksheeravrukshadravyas and indicated for Shotha. The Dravyas by its Guna Karma Vranashodana, Ropana, Yonidoshahara, Kandugna properties which helps to treatment of Kaphaja Yoni Vyapat. Hence here is an attempt to use Panchavalkala in Arka form and help the women kind as an easily available Ayurvedic vaginal wash in treating Vuvlo Vaginal Candidiasis.